A Simple Minimization Method of the Variables Number in Complete and Incomplete Logic Functions. Part 2 - Rytsar, B.Ye. (Управляющие системы и машины, 2017)
A new minimization method of the variables number in complete and incomplete logic functions, based on the procedure of conjuncterms splitting is proposed. The advantages of the proposed method are illustrated by examples of determining nonessential variables in the functions, which are borrowed from the well-known publications.